Participation of xCT in melanoma cell proliferation in vitro and tumorigenesis in vivo. (November 2018) - Shin, Seung-Shick; Jeong, Byeong-Seon; Wall, Brian; Li, Jiadong; Shan, Naing; Wen, Yu; Goydos, James; Chen, Suzie
Abstract Our research group demonstrated that riluzole, an inhibitor of glutamatergic signaling reduced melanoma cell proliferation in vitro and tumor progression in vivo. The underlying mechanisms of riluzole are largely unknown. Microarray analyses on two human melanoma cell lines revealed that riluzole stimulates expression of the cystine-glutamate amino acid antiporter, xCT (SLC7A11). Western immunoblot analysis from cultured human melanoma or normal melanocytic cells showed that xCT was significantly overexpressed in most melanomas, but not normal cells. Studies using human tumor biopsy samples demonstrated that overexpression of xCT was correlated with cancer stage and progression. To further investigate if xCT is involved in melanoma cell growth, we derived several stable clones through transfection of exogenous xCT to melanoma cells that originally showed very low expression of xCT. The elevated xCT expression promoted cell proliferation in vitro and inversely, these melanoma clones showed a dose-dependent decrease in cell proliferation in response to riluzole treatment. Xenograft studies showed that these clones formed very aggressive tumors at a higher rate compared to vector controls. Conversely, treatment of xenograft-bearing animals with riluzole down-regulated xCT expression suggesting that xCT is a molecular target of riluzole. Furthermore, protein lysates from tumor biopsies of patients that participated in a riluzole monotherapy phase II clinical trial showed a reduction in xCT levels in post-treatment specimens from patients with stable disease. Taken together, our results show that xCT may be utilized as a marker to monitor patients undergoing riluzole-based chemotherapies.